Prevention and resolution of land conflicts in the community in Suka Makmur Village - Wantu, Fence M.; Daud, Akbar Hudayatullah; Sarson, Mohamad Taufiq Zulfikar; Sarjono, Anastasia; Umar, Nurifana; Elmarianti; Aulia, Nur Insani (Edumedia Solution, 2026)
Land is a fundamental element with economic and social dimensions that are often a source of conflict due to the imbalance between the rule of positive Law (law in books) and practice in society (law in action). In Suka Makmur Village, low legal literacy and a strong tradition of underhand transactions create legal vulnerabilities and make land a